1994
DOI: 10.1128/jb.176.5.1374-1382.1994
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the indole-3-acetic acid biosynthesis pathway of Pseudomonas syringae pv. syringae affects growth in Phaseolus vulgaris and syringomycin production

Abstract: Homologs of the genes for indole-3-acetic acid (IAA) biosynthesis from Pseudomonas syringae pv. savastanoi were retrieved from a genomic library of P. syringae pv. syringae, and their nucleotide sequences were determined. Sequence relatedness between the P. syringae pv. syringae and P. syringae pv. savastanoi iaa operons is greater than 901% within the iaaM and iaaH loci but declines dramatically at a position approximately 200 bp 5' of the iaaM translation initiation codon. A third open reading frame was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 52 publications
1
43
2
1
Order By: Relevance
“…savastanoi (49). The genes in the operon are ÏŸ90% identical to those in the IAA operon of Pss Y30 (47). Although Pst DC3000 has no orthologs of iaaM and iaaH, it produces IAA (8), possibly due to PSPTO0517 and PSPTO0518, which have low sequence similarity to tryptophan monooxygenase and indoleacetamide hydrolase, respectively.…”
Section: Figmentioning
confidence: 96%
See 2 more Smart Citations
“…savastanoi (49). The genes in the operon are ÏŸ90% identical to those in the IAA operon of Pss Y30 (47). Although Pst DC3000 has no orthologs of iaaM and iaaH, it produces IAA (8), possibly due to PSPTO0517 and PSPTO0518, which have low sequence similarity to tryptophan monooxygenase and indoleacetamide hydrolase, respectively.…”
Section: Figmentioning
confidence: 96%
“…Auxin. Bacterial indole-3-acetic acid (IAA) can have either a stimulatory or inhibitory effect on plant growth depending on its concentration and the plant tissue exposed (47). Most pathovars of P. syringae produce IAA (48), but the amounts produced vary greatly between strains.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DC3000 does contain five nonribosomal peptide synthases in three separate gene clusters (PSPTO2829, -2830, -4518, -4519, and -4699) that may direct the biosynthesis of undescribed peptide or lipodepsipeptide products. Production of the phytohormone indole-3-acetic acid (IAA) by certain P. syringae pathovars has been shown to influence bacterial growth in planta and the expression of other virulence factors (47,48). The two genes required for IAA production, iaaH and iaaM, are present in DC3000.…”
Section: Ttss and Effectorsmentioning
confidence: 99%
“…In addition, R gene-mediated Xoo resistance accompanies the suppression of auxin signaling. A search of the amino acid sequences of Pseudomonas syringae pv syringae iaaH and iaaM (Mazzola and White, 1994) against the putative encoding products of the Xoo (strains KACC10331 and MAFF311018) whole genome sequence (Lee et al, 2005;Ochiai et al, 2005) did not reveal any homologous sequence. We then searched databases and found that Xoo carries NIT proteins (National Center for Biotechnology Information protein database accession numbers AAW74756, AAW74754, and YP_200139), which may contribute to the accumulation of IAA.…”
Section: Xoo Infection Induces Endogenous Synthesis Of Iaa In Ricementioning
confidence: 99%